2021
DOI: 10.3390/polym13162753
|View full text |Cite
|
Sign up to set email alerts
|

Healing Efficiency of CNTs-Modified-UF Microcapsules That Provide Higher Electrical Conductivity and EMI Shielding Properties

Abstract: In this study, the effect of the addition of multi-walled carbon nanotubes (MWCNTs), at three percentages, into the urea-formaldehyde (UF) shell-wall of microcapsules on the healing efficiency is reported. The modified shell-wall created a conductive network in semi-conductive epoxies, which led to an improvement of the electromagnetic interference shielding effectiveness (EMI SE); utilizing the excellent electrical properties of the CNTs. The microcapsule’s mean diameter and shell wall were examined via scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The microcapsules were manufactured according to our previous studies via the in situ emulsification polymerization method [ 12 , 13 , 37 ]. Two types of microcapsules were produced for the tests, neat (with a neat healing agent) and nanomodified (with a nanomodified healing agent).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microcapsules were manufactured according to our previous studies via the in situ emulsification polymerization method [ 12 , 13 , 37 ]. Two types of microcapsules were produced for the tests, neat (with a neat healing agent) and nanomodified (with a nanomodified healing agent).…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of external sensors either on top or inside the composite can degrade the structural performance since the sensors may act as damage initiation sites or internal defects [ 9 , 10 ]. In this case, many researchers have focused on the development of smart materials, and led to the production of structures with various functionalities, such as self-sensing [ 11 ], self-healing [ 12 , 13 ], electromagnetic shielding [ 13 ], energy harvesting [ 14 , 15 ], etc. Self-sensing is a valuable capability since the composite can identify internal deformations [ 16 , 17 ] and in-service damages [ 11 , 18 ], as well as additional functionalities such as curing monitoring [ 19 ] without the usage of external or embedded sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The repair efficiency is defined as the ability of a 3R composite to regain its initial mechanical properties [13][14][15][16][17][18][19] and is calculated according to Equation (4).…”
Section: Evaluation Of the Knockdown Effect And Repair Efficiencymentioning
confidence: 99%
“…The prerequisites for advanced composites, apart from high specific properties, are typically high fracture toughness and good fatigue performance. On the other hand, advanced functionalities include structural health monitoring (SHM) capability [5][6][7], electromagnetic shielding [8], energy harvesting [9][10][11][12], and self-healing capability [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes improved the heat resistance and storage modulus of PPF-CNTs nanocomposites. Kosarli et al (2021) added multi-walled carbon nanotubes to urea-formaldehyde resin microcapsules, and studied the effect of multi-walled carbon nanotubes on the healing rate of microcapsules. The study found that the introduction of 0.5% w/v CNTs did not change the healing rate of microcapsules, but it increased the mechanical properties of epoxy resin.…”
Section: Introductionmentioning
confidence: 99%